2001
DOI: 10.2307/3558396
|View full text |Cite
|
Sign up to set email alerts
|

Thrips pollination of androdioeciousCastilla elastica(Moraceae) in a seasonal tropical forest

Abstract: Androdioecy is a rare sexual system in nature, as predicted theoretically. Among the androecious species reported so far, Castilla elastica (Moraceae) is unique in that flowers are unisexual and staminate and pistillate flowers on cosexual plants are produced on different inflorescences. In addition, inflorescence structure of staminate inflorescences on males and staminate and pistillate inflorescences on cosexes is markedly different. Staminate inflorescences on males are bivalvate, while staminate infloresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 51 publications
2
78
0
5
Order By: Relevance
“…Hood (1935) on a unique specimen from Panama and posteriorly a second female was collected in Costa Rica (Mound and Marullo 1996). Recorded as a pollinator of Castillia elastica (Moraceae) in Panama (Sakai 2001 Mound and Marullo (1996) collected both sexes in flowers of Vaccinium consanguineum (Ericaeae) in Panama.…”
Section: Frankliniella Curiosa Priesner 1932mentioning
confidence: 99%
“…Hood (1935) on a unique specimen from Panama and posteriorly a second female was collected in Costa Rica (Mound and Marullo 1996). Recorded as a pollinator of Castillia elastica (Moraceae) in Panama (Sakai 2001 Mound and Marullo (1996) collected both sexes in flowers of Vaccinium consanguineum (Ericaeae) in Panama.…”
Section: Frankliniella Curiosa Priesner 1932mentioning
confidence: 99%
“…In contrast to the notion that anemophily is a rare phenomenon in tropical wet forests, several studies and authors have demonstrated the occurrence of this pollination strategy in a large number of tree and herbaceous species (Lewis 1986. Sakai 2001.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics, wind-dispersed plants are less numerous and diverse compared to temperate zones (Sakai 2001). Anemophilous pollination in angiosperms is a derived characteristic that has arisen, in an independent manner, 65 times during the evolutionary history of these plants and is present in 10% of the species in this plant group (Ackerman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previously known only in a few plants (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and invertebrate animals (11)(12)(13)(14)(15), androdioecy has also evolved independently in a vertebrate species: the mangrove killifish, Kryptolebias (formerly Rivulus) marmoratus. Most surveyed populations of K. marmoratus consist primarily or exclusively of hermaphroditic individuals, but gonochoristic males are observed occasionally, and recent genetic evidence suggests that such individuals may mediate infrequent outcross events in this otherwise self-fertilizing species (16)(17)(18).…”
mentioning
confidence: 99%